Cryopreservation Current Advances and Evaluations - Quain, Marian (IntechOpen, 2020)
Cryopreservation - Current Advances and Evaluations sheds light on storage of cells at subzero temperatures while ensuring that biological functionality is not compromised. Cryopreservation presents a perfect technique by which life can be preserved for posterity. However, there are many challenges to overcome and questions to answer, such as: Are organisms and metabolic systems functioning normally after cooling and thawing? This book provides comprehensive information on cryopreservation with a particular focus on cryoprotectant agents (CPAs). CPAs prevent ice from forming on cryogenically preserved cells, tissues, and organs, but can become toxic at high concentrations. As such, more research is needed to determine their precise mechanisms of action and to develop potential new CPAs that will not compromise the biology of cells. This book is an attempt in this direction.